Epidemiological Impact of Neurodegenerative Diseases in the Rural Spanish-Portuguese Cross-Border Region - Alonso-Sardón, Montserrat; Paulino, Manuel; Fernandes, Adília; Martín-Delgado, María Antonia; Pérez-Martín, Raixa Noemí; Magalhães, Carlos Pires; Pimentel, Helena; Mata, Augusta; Silvano, Justina; Corte, Agostinha; Paiva, Teresa; Marques, Ermelinda (Neuro-degenerative diseases, 2023)
Epidemiological data indicate that neurodegenerative diseases show a high prevalence with a progressive increasing trend, especially in aging populations, as is the case in rural areas. The objective of this study was to assess the quantitative impact of neurodegenerative diseases in rural areas of the Spanish-Portuguese border region and to describe the epidemiological profile of the most prevalent disorders in one of the most depopulated and aged regions of Europe. A cross-sectional descriptive study was designed to estimate the prevalence of subjects diagnosed with the most common neurodegenerative disorders: dementia (Alzheimer's disease and other dementias), Parkinson's disease and Parkinsonism, and multiple sclerosis in the Spanish-Portuguese cross-border border region in 2020. It includes Bragança and Guarda Districts (Portugal) and Salamanca (Castilla y León, Spain). Neurodegenerative diseases accounted for 1.85% in the Spanish-Portuguese cross-border region in 2020; a total of 5,819 records were reported: 987 (prevalence, 2.51%) in Salamanca (Spain); 2,332 (prevalence, 1.87%) in Bragança; and 2,500 (prevalence, 1.66%) in Guarda. Female population suffered from them in higher proportion (2.35 vs. 1.32%). Dementia represented 1.19% (3,744), Parkinson's disease and Parkinsonism 0.58% (1,823), and multiple sclerosis 0.08% (252). These disorders impacted older age groups. In the rural border region of Spain, 1 out of 4 cases were institutionalized. The findings reveal the health impact of neurodegenerative diseases in the Spanish-Portuguese cross-border region. The epidemiological data emphasize the region's circumstances and highlight research priorities. Intervention strategies must be implemented in the region to ensure quality healthcare in rural areas.